Comparing hybrid welfare systems: The differentiation of health and social care policies at the regional level in Italy - Bertin, Giovanni; Pantalone, Marta (Italian Sociological Review, 2018)
Welfare-state research has traditionally been centered on national states, while regional differences have received less attention. This article analyzes local welfare policies in 20 Italian regions using data in 2005 and 2010. We use factor and cluster analysis and typological classifications on institutional data concerning two areas of intervention, social care and healthcare policies. The results show that the Italian welfare system is a hybrid and is differentiated both across regions and policies. By using a regional perspective, we highlight the need to consider the subnational level as central to the construction of descriptive welfare typology.